Pengaruh Komitmen Organisasi, Pengalaman Kerja, Profesionalisme dan Pendidikan, Terhadap Pertimbangan Tingkat Materialitas dalam Audit: (Studi Empiris Pada Auditor yang Bekerja di Kantor Akuntan Publik di Wilayah Jakarta Selatan dan Jakarta Barat) - Utari Nur Annisa; Anggoro Yuli Cahyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of organizational commitment, work experience, professionalism and auditor education on consideration of the level of audit methodology for auditors working in public accounting firms in the South Jakarta and West Jakarta regions in 2024. The data sampling technique involves distributing questionnaires directly to respondents. The research population was auditors who worked in 9 Public Accounting Firms and obtained 78 questionnaires and all questionnaires could be processed. The data processing used was multiple linear regression analysis, tested using the Statistical Package For The Social Science (SPSS) program version 22 and Microsoft Excel 2010. Based on the research results, it can be concluded that organizational commitment (X1) and auditor education (X4) have a significant effect on consideration of audit materiality level (Y), while work experience (X2) and professionalism (X3) have no effect on consideration of audit materiality level (Y).